Automatic Pet Feeder Using PIC - Mohd Azwan, Mokhtar (UTeM, 2010)
This project is about designing an automatic pet feeder that could automatically serves food to the pets. The title of this project is Automatic Pet Feeder Using PIC. The pet meals that will be served are from the small types because some studies have shown that feeding the pet with smaller meals over the course of the day can prevent pet obesity and lead the pets to better health. The user will specify when their pet will be fed. This automatic pet feeder uses a micro controller and it consists of an interface with buttons, liquid crystal display (LCD), RC servo motor and the hardware part. The RC servo motor shaft will be attached at one side of a feeding plate. When the servo motor runs, the feeding plate will spin which will turn pet food drops down through the perforated feeding bowl. So, the pets will receive regular amounts of food on a steady feeding schedule.